2021
DOI: 10.3390/nu13061749
|View full text |Cite
|
Sign up to set email alerts
|

Implications of SCFAs on the Parameters of the Lipid and Hepatic Profile in Pregnant Women

Abstract: Short-chain fatty acids (SCFAs) are the product of the anaerobic intestinal bacterial fermentation of dietary fiber and resistant starch. An abnormal intestinal microbiota may cause a reduction in the production of SCFAs, which stimulate the development of intestinal epithelial cells, nourish enterocytes, influence their maturation and proper differentiation, reduce the pH, and are an additional source of energy for the host. There have been reports of the special role of SCFAs in the regulation of glucose and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 56 publications
3
27
1
Order By: Relevance
“…Clinical and basic studies confirm that microbiota-derived propionate acts directly on intestinal γδ T cells, inhibiting their production of IL-17 and IL-22 mainly through a histone deacetylase-dependent manner ( Dupraz et al., 2021 ). Moreover, animal and human studies found that a similar increase in SCFAs protected liver function, reduced intestinal inflammation, and protected against colorectal cancer through regulating CRP level and hepatic lipid metabolism, decreasing proinflammatory Th1 and Th17 cells, and increasing anti-inflammatory immune cells ( Alrafas et al., 2020 ; Ziętek et al., 2021 ). Furthermore, LeBlanc et al.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical and basic studies confirm that microbiota-derived propionate acts directly on intestinal γδ T cells, inhibiting their production of IL-17 and IL-22 mainly through a histone deacetylase-dependent manner ( Dupraz et al., 2021 ). Moreover, animal and human studies found that a similar increase in SCFAs protected liver function, reduced intestinal inflammation, and protected against colorectal cancer through regulating CRP level and hepatic lipid metabolism, decreasing proinflammatory Th1 and Th17 cells, and increasing anti-inflammatory immune cells ( Alrafas et al., 2020 ; Ziętek et al., 2021 ). Furthermore, LeBlanc et al.…”
Section: Discussionmentioning
confidence: 99%
“…The study identification, selection, and inclusion process are summarized in Figure 2 . After eliminating duplicates, in total, 139 articles were included in this review, 112 from the first search term containing obesity [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , ...…”
Section: Methodsmentioning
confidence: 99%
“…A recent clinical study found that pregnancy-associated obesity was associated with significant reduction of SCFAs which affect the liver function parameters [ 41 ]. Moreover, in patients with Parkinson’s disease, the level of SCFAs was altered, especially propionic acid [ 42 ].…”
Section: Discussionmentioning
confidence: 99%